Effect of Relative Humidity on Gloss of Preservative Treated Finished Wood - Samani, Ajmal; Gupta, Sachin (Indian Forester, 2010)
The effect of relative humidity on performance of different finishes is evaluated on preservative treated mango wood on the basis of gloss values. Per cent loss in gloss of samples finished with clear varnish is much higher than other finishes applied on preservative treated samples. A comparison of loss in gloss values with and without preservative treatment is also reported. The per cent loss of gloss is least in the case of linseed oil polished samples.